A combined framework for the life cycle assessment and costing of food waste prevention and valorization: An application to school canteens - Fabio De Menna; Jennifer Davis; Karin Östergren; Nicole Unger; Marion Loubiere; Matteo Vittuari (Agricultural and Food Economics, 2020)
About one third of global edible food is lost or wasted along the supply chain, causing the wastage of embedded natural and economic resources. Life cycle methodologies can be applied to identify sustainable and viable prevention and valorization routes needed to prevent such inefficiencies. However, no systemic approach has been developed so far to guide practitioners and stakeholders. Specifically, the goal and scoping phase (e.g. problem assessed or system function) can be characterized by a large flexibility, and the comparability between food waste scenarios could be not ensured. Within the Horizon2020 project Resource Efficient Food and dRink for the Entire Supply cHain, this study aimed to provide practitioners with guidance on how to combine life cycle assessment and environmental life cycle costing in the context of food waste. Recent literature was reviewed to identify relevant methodological aspects, possible commonly adopted approaches, main differences among studies and standards and protocols, main challenges, and knowledge gaps. Basing on this review, an analytical framework with a set of recommendations was developed encompassing different assessment situations. The framework intends to provide a step by step guidance for food waste practitioners, and it is composed of a preliminary section on study purpose definition, three decision trees-respectively on assessment situation(s), costing approach, and type of study (footprint vs. intervention)-and two sets of recommendations. Recommendations can be applied to all levels of the food waste hierarchy, stating a generic order of preference for handling food chain side flows. This consistent and integrated life cycle approach should ensure a better understanding of the impact of specific interventions, thus supporting informed private and public decision making and promoting the design of sustainable and cost-efficient interventions and a more efficient food supply chains.
Keywords: 330; Life cycle costing; Life cycle assessment; Food waste; Food loss; E-LCC; LCA; REFRESH